High-density rearing of red-bellied pacu in two closed systems - Poleo, Germán; Aranbarrio, José Vicente; Mendoza, Lismen; Romero, Oneida (Pesquisa Agropecuária Brasileira, 2011)
The objective of this work was to evaluate the tolerance of red‑bellied pacu, Piaractus brachypomus, to high‑density in closed production systems. Nine hundred fingerlings with 44.3±26 g weight were distributed in six 4.8 m3 concrete tanks. Three tanks had zero water exchange rate (SCR), and in the other three water was connected to a bioclarifier (SRA). All tanks had strong aeration to keep solids suspended and air supply to the system. Fish were fed to satiety for 192 days with a commercial feed. Water quality parameters such as dissolved oxygen, total ammonia nitrogen, nitrites, nitrates, alkalinity, hardness, temperature and pH were measured weekly. Fish in the SCR had an average growth rate of 2.34±0.05 g per day, showed a food conversion rate of 1.5±0.06, reached a final density of 12.96±0.53 kg m-3, and a final weight of 449.5±99 g. In the SRA, fish grew at 2.33±0.03 g per day, had a food conversion rate of 1.6±0.07, reached a final average density of 12.13±1.12 kg m-3 and a final weight of 446.5±10 g. Red‑bellied pacu can be grown in closed systems with zero water exchange at high culture densities.